Designing of YVO4 supported β-AgI nano-photocatalyst with improved stability. Issue 1 (1st December 2014) - Vignesh, K.; Suganthi, A.; Min, Bong-Ki; Rajarajan, M.; Kang, Misook
Abstract : The proposed schematic diagram of electron transfer in AgI–YVO4 for the photodegradation of Rh-B under simulated solar light irradiation. Abstract : Yttrium ortho vanadate supported β-silver iodide nanoparticles (AgI–YVO4 ) were designed by a sono-chemical deposition method. The structural, morphological and optical properties of the as-prepared nanoparticles were investigated in detail. Transmission electron microscopy (TEM) results revealed that AgI nano-sheets were attached to YVO4 nano-grains. UV-vis-DRS results indicated that the visible light absorption ability of YVO4 was promoted by AgI modification. The photocatalytic activity was evaluated for the degradation of rhodamine-B (Rh-B) dye under simulated solar light irradiation. The photocatalytic activity of YVO4 was strongly influenced by the concentration of AgI. The photocatalyst of 10% AgI–YVO4 exhibited the best performance (98%) for the degradation of Rh-B. Moreover, the photocatalytic activity was well maintained even after four cycles. The results of this research work would be very useful for the degradation of harmful organic dyes in aqueous environments.